English in rural schools: to teach it or not, that is the dilemma - Velasquez, Silvina (Subcomité editorial y de evaluación de obras de la Facultad de Ciencias de la Salud Editora Revista Dra. Bibiana Matilde Bernal Gómez, 2020)
The objective of this presentation is to shed light on the difficulties that rural teachers from Colombian public schools have when teaching English, using their own voices to do so, and also, to put forward possible solutions regarding this recurrent problem. The methodology used was that of observation, the results of which were written down in a journal. In addition, several interviews and surveys were conducted with teachers in Boyacá and Santander. Most of the educators who were consulted are aware of their limitations when it comes to teaching a foreign language. Very few of them have the necessary training to give the classes and reach the objectives set for them, in some cases due to a lack of resources and time, and in others simply because they do not feel capable of learning the language. Furthermore, the majority of the teachers surveyed agreed that the objectives that schools and the Ministry for Education insist upon are not always realistic and the results expected are, in most cases, almost impossible to attain. Many teachers who work in rural schools do not feel prepared to teach English and that leads them to one of three scenarios: to teach what they know, to the extent that they can and with the few resources they have; to hire a third party to teach the English class; or to reduce the number of hours devoted to the English language to a minimum. This is translated into inefficient training and a reluctance on the part of the students to study the language, thus, disregarding the importance that a second language holds in academic and professional life today.